Three cases of canine babesiosis caused by Babesia odocoilei-like parasites in Japan. (October 2021) - Yamasaki, Masahiro; Nukada, Yuka; Ito, Minori; Uchida, Naohiro; Iguchi, Aiko; Inokuma, Hisashi
Abstract: Babesia odocoilei -like parasites were first reported in 2003, and their virulence and hosts remain unknown. We report three cases of dogs with canine babesiosis in Iwate Prefecture. Since Iwate Prefecture area is an area of Japan where canine babesiosis is not endemic, we suspected that these cases of canine babesiosis were caused by B. odocoilei -like parasites. In the present study, we tried to identify the Babesia species that caused these cases of canine babesiosis. To classify Babesia parasites, the heat shock protein 70 ( HSP70 ) gene was examined. Accordingly, we cloned and analyzed the HSP70 gene sequences of B. odocoilei -like parasites from three Ixodes ovatus ticks. It was determined that the nucleotide sequence of the HSP70 gene of the B. odocoilei -like parasites was not consistent with that of B. odocoilei, which suggests that these parasites were from a different species than B. odocoilei . Second, we identified the Babesia species that infected the three dogs by using the HSP70 gene and 18S rRNA. A partial HSP70 gene of B. odocoilei -like parasites was detected in the three dogs, but that of B. gibsoni was not detected. Additionally, a partial sequence of 18S rRNA of B. odocoilei -like parasites was detected in two dogs. These results demonstrated that two dogs were certainly infected with B. odocoilei -like parasites and that one dog was probably infected with B. odocoilei -like parasites. Therefore, these dogs were diagnosed with canine babesiosis due to the presence of B. odocoilei -like parasites. As there were only three cases, additional cases are needed to confirm our findings. Graphical abstract: Unlabelled Image Highlights: HSP70 gene of B. odocoilie -like parasites was cloned. B. odocoilei-like parasites are different from B. odocoilei and B. divergens. Three dogs with canine babesiosis were found in northeast Japan. HSP70 gene and 18S rRNA of B. odocoilei -like parasites were detected from three dogs. Three dogs were diagnosed with canine B. odocoilei -like infection.